A Novel Exact Solution of Longshore Current and Its Application on Permeable Groin - Umar, Hasdinar; Assidiq, Fuad M.; Triatmadja, Radianta; Baeda, Achmad Y. (Salehan Institute of Higher Education, 2025)
One major environmental problem exacerbated by longshore currents is beach erosion. Groins are a common defense tactic built perpendicular to the shore. However, conventional impermeable groins promote downstream erosion and disrupt sediment movement. Permeable groins provide a more environmentally friendly option, allowing some sediment to flow through. This study examines the effects of permeable groins on longshore currents. Permeable groins are not included in currently used longshore current equations. This study fills this gap by creating a new longshore current velocity equation considering permeable groins. The longshore current equation with the groin was developed based on the momentum equation in the longshore direction without the influence of lateral mixing and the assumption that base friction will rise due to the groin. Therefore, it was determined that the base shear stress after the groin was equal to the base shear stress plus the drag caused by the groin. The result shows that the longshore current equation through the groin is a function of the breaking wave parameter and the resistance parameter owing to the groin. Longshore current velocities with and without permeable groins of different densities were measured in wave basins. We collected information on groin characteristics, current velocities, and breaking wave heights. This investigation validates the shortcomings of the current equations. Doi: 10.28991/CEJ-2025-011-02-07 Full Text: PDF